Crop Regulation in Guava: A review - Mishra, D.S.; Singh, A.K. (Annals of Arid Zone, 2023)
Guava (Psidium guajava L.), commonly known as Apple of Tropics andsubtropics. Amongst various tropical and sub-tropical fruit crops like guava grown inIndia, if left on its own, give several light crops of the variable quantities and qualitiesfrom the various flowering flushes throughout the year. Therefore, to obtain higher fruityield during a particular period, bearing guava trees are given a resting period withartificial means so that the natural flowering tendency of the trees is altered. This can beachieved through root exposure and its pruning, shoot pruning, withholding irrigationwater, deblossoming, chemicals/PGRs application and shoot bending. Regulated cropsare desired to avoid glut in the market and also ensure the regular supply of fruits.The basic principle of crop regulation is to induce flowering and fruiting in desiredseason of the year that contribute to increased fruit yield, quality, profitability andsustainability of the environment by reducing the use of the frequency of the pesticides.Among various chemicals used NAA (600-800 ppm) and urea (10-15%) could be widelyused in different agro-climatic conditions for crop regulation in guava.